A Model of Protection and the Exchange Rate - Johnson, Harry G. (Review of Economic Studies, 1966)
Journal Article A Model of Protection and the Exchange Rate Get access Harry G. Johnson Harry G. Johnson The University of Chicago and The Brookings Institution Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 2, April 1966, Pages 159–163, https://doi.org/10.2307/2974439 Published: 01 April 1966